EDUCATION AND JOB MATCH : THE RELATIONSHIP OF EDUCATION AND EMPLOYMENT IN SOKO TUBAN DISTRICT - Handoko, Handoko Sosro Hadi Wijoyo; Ulfaida, Afifa (Universitas Islam Lamongan, 2024)
This study aims to determine the effect of education and soft skills on employment in the District of Soko Tuban, both partially and simultaneously. It employs a descriptive quantitative approach, targeting high school graduates up to bachelor's degree holders in Soko District, with a sample size determined using the Slovin formula. Primary data was collected from 99 respondents through questionnaires using purposive sampling. Data was analyzed using multiple linear regression